Pengaruh Pembelajaran Kearifan Lokal di Jawa Barat dalam Melestarikan Budaya Tradisional bagi Siswa SD - Rahmiati, Devi; Suharini, Erni; Widiyatmoko, Arif (FONDATIA, 2025)
This study is motivated by the declining understanding of Sundanese traditional culture among elementary school students in West Java, caused by globalization and the suboptimal implementation of local wisdom-based learning in schools. The research aims to analyze the influence of local wisdom-based learning on the preservation of traditional culture using a quasi-experimental method with a pretest-posttest nonequivalent control group design. The study involved 50 fourth-grade students randomly divided into two groups: an experimental group of 25 students and a control group of 25 students from one elementary school in Bandung City. Data were collected through cultural knowledge tests, attitude assessments, and observation sheets during three sessions of integrated local wisdom-based learning (e.g., folktales, traditional games, Sundanese arts). The data were then analyzed using t-tests and N-gain analysis. The results of the study showed that there was a significant increase in the experimental group in the knowledge test, with an N-gain of 0.66 or 66% in the moderate category, an increase in attitude assessment of 26%, and an increase in skill observation results of 29%. The main findings prove that local wisdom-based learning is effective in preserving traditional culture while improving student learning outcomes. The study concludes that integrating local content into the elementary curriculum through the development of contextual modules, teacher training, and collaboration with cultural communities is essential. The implications of this research provide empirical evidence for strengthening character education based on local wisdom and formulating educational policies oriented toward cultural preservation in West Java.